Life History, Population Dynamics and Production of Pontoporeia hoyi (Crustacea, Amphipoda) in Relation to the Trophic Gradient of Lake George, New York - C. A. Siegfried (Hydrobiologia, 1985)
The life history characteristics, population dynamics and production of Pontoporeia hoyi in Lake George, New York, were studied from May 1981 through October 1982. P. hoyi, in terms of both density and standing crop, is the most prevalent member of the deep water macrobenthos of Lake George. It reproduces in the winter, with young being released in the late winter-early spring. At the southernmost study site, young released in the spring grew to 6–7 mm in length and bred during their first winter. At the remaining sites, P. hoyi required two years to complete its life cycle. This difference in life history characteristics can be related to food availability and temperature differences. The open waters of the south end of Lake George are not only more productive but are also more closely associated with the littoral zone, providing a wealth of bacteria-rich detritus for benthic deposit feeders. The greater food availability in the south basin of Lake George is reflected in significantly larger brood sizes and smaller size at maturity for P. hoyi populations from the south end of the lake. The southernmost study site has significantly greater P. hoyi density and standing crop than all other sites. The cohort of the year dominated density and standing crop at the southern site while the cohort of the previous year dominated standing crop at the other sites. Peak abundance ranged from 600 · m−2 at the north site to 2 900 · m−2 at the south site. Cohort production ranged from ∼2g · m–2 at the north site to ∼15g · m−2 at the south site.
Keywords: Amphipoda; benthos; life history; Pontoporeia hoyi; production